Some passages in the life of Mr Adam Blair, Minister of the Gospel at Cross-Meikle - Lockhart, J. G. (John Gibson), 1794-1854; Richardson, Thomas C. (Edinburgh : Edinburgh University Press, 2020)
This edition provides the first modern publication of Lockhart's final text, the revised second edition (1824), as well as the first scholarly edition of the novel, including extensive annotations and a detailed textual history.
Intro -- Contents -- Aims of the Edition -- Volume Editor's Acknowledgements -- Introduction -- 1. Genesis of the Novel -- 2. Critical Reception -- 3. 'What new character has he given us?' -- 4. Essay on the Text -- Some Passages in the Life of Mr Adam Blair -- Appendix: 'Hints for a Young Author, from A Very Old One' -- Emendation List -- Hyphenation List -- Explanatory Notes -- Textual Notes -- Glossary
Print version record.
JSTOR
Keywords: Scotland -- Fiction; Écosse -- Romans, nouvelles, etc; Scotland; Fiction